STRATEGI PEMBELAJARAN PKN YANG MENYENANGKAN UNTUK SISWA SEKOLAH DASAR - Damayanti, A. Alfiani; Khaedar, Muh. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Civic Education (PKn) at the elementary school level plays a strategic role in instilling national values and shaping the character of responsible and active citizens from an early age. However, its implementation in the field is often still conventional and monotonous, thus requiring new approaches that are more engaging and meaningful. This study aims to identify enjoyable Civic Education learning strategies that align with the characteristics of elementary school students. The method used is a literature review by examining various national and international references. The discussion reveals that strategies such as Project-Based Learning, collaborative learning, role play, the use of educational technology, and differentiated instruction are effective in enhancing student participation, understanding, and internalization of civic values. In addition, the implementation of these strategies faces challenges such as limited teacher competence, inadequate facilities, and classroom management issues. Therefore, systemic support from schools, governments, and the community is needed to create Civic Education learning environments that are active, relevant, and enjoyable.